Design Of Procedure To Fulfill Prime 3 Certification Using Clear Method For Land Preparation And Plant Protection Process In Abo Farm Small Medium Enterprise - Juli Trisna Aisyah Sinaga; Yati Rohayati; Atya Nur Aisha (eProceedings of Engineering, 2015)
ABOFARM is one of SME that applies pesticide application and cultivation with wise. This SME want to get Prime 3 Certification but have limited information, record, and procedure to fulfill the requirement. Therefore, the research is carrying out to formulate the design of procedure that are effective, efficient, and implement by ABO FARM SME in Ciwidey. This SME want to get Prime 3 Certification to enter modern market. Therefore, the research uses CLEAR Method to map the business process in ABO FARM SME. Method to collects data are in-depth interview and observation. In addition, the research is also uses data from books literature, scientific publications, magazine published by the government, and website that have reliable information. From this research, provide results and evaluate of existing conditions that exist in ABO FARM SME. There are two processes must be evaluated to fulfill the requirements in Prima 3 Certification. Then provide the design of procedure utilizing results of business processes mapping. There are two procedures designed in this research. The contents from this procedure include of benefit, definition, reference, process description, performance measurement, record, and related document. Keywords: Design of Procedure, CLEAR Method, Prime 3 Certification.